Burger King’s Goodvertising Campaign Analysis in the Pandemic Era: (Study on Posts of Calls to Buy Competitors’ Products on Instagram Account @burgerking.id) - Nabila Fitrianti; Muhamad Sazali; Dika Nanda Kinanti (Universitas Terbuka, 2022)
There are many business competitions spread around in public. In order to be the top-of-mind in the competition, brands must be able to create unique selling propositions (USP) to be remembered by the public. Several approaches are popular and able to attract people’s attention, one of which is goodvertising, where brands emerge by communicating their concerns and attention to social issues. One brand that has recently used the goodvertising strategy is Burger King Indonesia. Amid the COVID-19 pandemic hitting the economies of many parties, Burger King launched a campaign on its Instagram @burgerking.id with the message to buy products from its competitors. It is interesting to see how the goodvertising strategy is used by Burger King Indonesia, combined with the concept of viral advertising. Through this qualitative research with a constructivist paradigm, with this case study research method, it is found that in the pandemic era, with the most significant internet users and Burger King consumers tend to be millennials, the goodvertising strategy carried out by Burger King Indonesia, combined with E-WOM and the viral advertising, provides a significantly good impact for the rise of the brand image in society. In addition, the increase in the brand image of Burger King can also be seen in the participation of the general public in voicing, sharing, and reuploading related McDonald’s campaigns with the creation of the hashtags #pesandarimcdonalds and #pesanlahdarimcdonald on Instagram. Hence, this can be seen from the increase in community involvement in their social media accounts, as well as a large number of publications on earned media such as detik.com for free